WORKSHOP PENYUSUNAN BUTIR SOAL HOTS (HIGH ORDER THINKING SKILL) DAN EVALUASINYA DI UPT SDN 145 GRESIK - Feny Rita Fiantika; Triman Juniarso; Dian Kusmaharti; Reza Rachmadtullah; Apri Irianto (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2023)
Abstract: PISA 2022 results for mathematics literacy in figure 1 show an increase of 5 positions, scientific literacy in figure 2 shows an increase of 6 positions and reading literacy shows an increase of 5 positions compared to PISA 2018. The results of interviews with 10 teachers in Gresik district stated that teachers experienced difficulty in composing HOTS type questions and confusion between Bloom's taxonomy and Anderson's taxonomy. Teachers experience difficulty in compiling HOTS type objective questions. This is a very urgent problem and needs to be addressed immediately. For this purpose, the PGSD community service team at PGRI Adi Buana Surabaya University carried out community service for the Gresik Elementary School Teacher Working Group (KKG) in the Gresik area, providing a workshop on preparing HOTS questions and evaluating them. A total of 24 representative teachers from schools throughout Gresik district attended the event. At the end of the activity, a response questionnaire will be given regarding the implementation of the workshop activities. The results obtained were that the teacher was able to create questions with the help of these operational verbs well, the Context Dependent Item Sets prepared by the teacher had the theme of Traditional Markets, Parks, Culture and Malls, and more than 50% of workshop participants had experienced an increase in understanding about compiling HOTS material.            Keywords: high order thinking skill; context dependent item sets Abstrak: Hasil PISA 2022 literasi matematika pada gambar 1 menunjukkan kenaikan 5 posisi, literasi sains pada gambar 2 menunjukkan kenaikan 6 posisi dan literasi membaca menunjukkan kenaikan 5 posisi dibandingkan PISA 2018.  Hasil wawancara 10 orang guru di kabupaten Gresik menyatakan bahwa guru mengalami kesulitan dalam menyusun soal bertipe HOTS dan bingung membedakan taksonomi Bloom dan taksonomi Anderson. Guru mengalami kesulitan dalam menyusun soal objektif bertipe HOTS. Hal ini merupakan masalah yang sangat urgent dan perlu segera ditanggani. Untuk kepentingan tersebut di atas tim pengabdian masyarakat PGSD Universitas PGRI Adi Buana Surabaya melakukan pengabdian masyarakat bagi Kelompok Kerja Guru (KKG) Sekolah Dasar wilayah Gresik memberikan workshop penyusunan soal HOTS dan evaluasinya. Sebanyak 24 guru perwakilan dari sekolah se-kabupaten Gresik hadir dalam acara tersebut. Di akhir kegiatan akan diberikan angket respon berkaitan dengan pelaksanaan kegiatan workshop. Hasil yang diperoleh adalah guru dapat membuat soal dengan bantuan kata kerja operasional tersebut dengan baik, Context Dependent Item Sets yang disusun guru bertema Pasar Tradisional, Taman, Budaya dan Mall, dan lebih dari 50% peserta workshop telah mengalami peningkatan pemahaman tentang menyusunan materi HOTS. Kata kunci: high order thinking skill; context dependent item sets